2022
DOI: 10.21203/rs.3.rs-1610261/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of urinary function recovery after radical prostatectomy

Abstract: Purpose: Even in the era of laparoscopic radical prostatectomy (LRP) and robot-assisted laparoscopic radical prostatectomy (RALP), we sometimes experience patients with severe urinary incontinence after surgery. The aim of this study was to identify the predictors of urinary continence recovery among patients with urinary incontinence immediately after surgery (UIIAS).Methods: We identified 274 patients with clinically localized prostate cancer who underwent LRP and RALP between 2011 and 2018. UIIAS was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Dr. Hakozaki and collegues from Japan performed in page 50 ( 4 ) a nice study about the predictors of urinary function recovery after laparoscopic and robotic-assisted radical prostatectomy and concluded that younger patients and patients with higher intraoperative blood loss recover urinary continence one year after surgery even if they are incontinent immediately after surgery.…”
mentioning
confidence: 99%
“…Dr. Hakozaki and collegues from Japan performed in page 50 ( 4 ) a nice study about the predictors of urinary function recovery after laparoscopic and robotic-assisted radical prostatectomy and concluded that younger patients and patients with higher intraoperative blood loss recover urinary continence one year after surgery even if they are incontinent immediately after surgery.…”
mentioning
confidence: 99%